Implementation of Lean Manufacturing tools in manufacturing industries: a literature Review [Implementación de herramientas de Lean Manufacturing en industrias manufactureras: una revisión de la literatura - De la Cruz-Felipe, Caroline Pamela (2021)
Manufacturing industries develop in a competitive environment, standing out those that make the right decisions to improve their processes. This study analyzed scientific publications related to the influence of Lean Manufacturing's tool implementation in manufacturing industries productivity. The information sources used were: EBSCO, ProQuest, Redalyc, Dialnet, Microsoft Academic and Google Academic; of which 25 publications could be obtained through proposed inclusion and exclusion criteria and the application of the PRISMA and PICO strategies. The publications analyzed indicated that the implementation of various Lean Manufacturing tools have a positive influence on productivity, which is manifested in: reduction of times, waste and failures.